2D Materials for Nonlinear Photonics and Electro‐Optical Applications. Issue 14 (17th June 2021) - Yin, Peng; Jiang, Xiantao; Huang, Rui; Wang, Xin; Ge, Yanqi; Ma, Chunyang; Zhang, Han
Abstract: 2D materials have received significant attention from the scientific community due to their unique structures and excellent physical properties. A lot of applications are explored based on graphene, topological insulators, and transition metal dichalcogenides. With further development of 2D materials, other Group‐VA materials such as titanium carbide and MXenes also show potential advantages in several important applications. Therefore, it is indispensable to investigate the properties and applications of 2D materials comprehensively. In this review, the fabrication methods of 2D materials are introduced systematically. The nonlinear optical properties of 2D materials including Kerr effect, saturable absorption, carrier dynamics, and other nonlinear effects are summarized in detail. Based on this, several electro‐optical applications are reviewed. Finally, future perspectives of 2D materials in electro‐optics are presented. Abstract : 2D materials for nonlinear photonics and electro‐optical applications are reviewed. First, the fabrication methods of 2D materials are introduced systematically. The nonlinear optical properties of 2D materials including Kerr effect, saturable absorption, carrier dynamics, and other nonlinear effects are summarized in detail. Based on this, several electro‐optical applications are reviewed.